Endodontics - Stock, Christopher; Gulabivala, Kishor (Elsevier-Mosby, 2004)
This lavishly illustrated, practical guide to endodontic treatment and procedures covers the latest developments in instrumentation and filling techniques * Includes 1,600 superb illustrations, with color coded line diagrams that present clinical, diagnostic, and practical information in an easy-to-follow manner. * Provides a full chapter on radiography to emphasize its importance in both diagnosis and treatment.
Keywords: endodoncie; zubní lékařství; Endodontics